Bridging Innovation, Prevention, and Holistic Practice in Primary Health Care - Yogi Fitriadi (Review of Primary Care Practice and Education (Kajian Praktik dan Pendidikan Layanan Primer), 2026)
It is a great privilege to present this latest issue, which brings together a collection of research articles, a concept paper, and a compelling case report. The unifying thread of this edition is the imperative to strengthen primary health care as the frontline of clinical medicine and public health. From leveraging family dynamics and digital tools to refining diagnostic accuracy and empowering marginalized youth, the contributions in this volume reflect a dedicated push toward comprehensive, patient-centered care across diverse populations. Primary health care delivery in Indonesia continues to face numerous challenges, wherein the family plays a crucial role in enhancing patient quality of life. The family's involvement in supporting patient treatment is paramount, as family members serve as the patient's primary caregivers. Within the framework of family medicine, the family is not merely a patient's social background, but a vital partner actively engaged in every stage of clinical management. As the fundamental biopsychosocial unit, optimal family functioning provides essential emotional support, ensures the continuity of medical interventions, and enhances treatment adherence, particularly among individuals with chronic conditions. Through a family-centered care approach, family physicians leverage family structure and dynamics to reinforce health education, mitigate psychosocial barriers, and establish sustainable support systems to achieve optimal clinical outcomes and improve overall quality of life. Primary health care is further reinforced by the role of digital health in empowering both patients and their families. In family medicine practice, the integration of digital health serves as a primary accelerator for holistic patient and family empowerment. By utilizing telemedicine platforms, application-based self-monitoring, and integrated medical information access, digital technologies transcend conventional clinical boundaries by shifting the locus of care into the home environment. This approach facilitates more efficient bidirectional communication between family physicians and the patient’s biopsychosocial unit, fosters active family participation in shared decision-making, and promotes health literacy. Consequently, digital health not only strengthens treatment compliance and therapeutic efficacy, but also transforms patients and families from passive recipients of care into empowered, autonomous partners in managing their health sustainably. The scope of digital health in health care delivery continues to expand, as evidenced by the proliferation of telemedicine services and targeted digital health education designed to manage health behaviors and chronic conditions, such as adolescent smoking behavior and diabetes mellitus. We extend our sincere gratitude to all contributing authors for sharing their work, as well as to our peer reviewers for ensuring the scholarly standards of this journal. We trust that these findings will inform clinical practice, inspire further research, and support evidence-based decisions across primary care systems.Yogi Fitriadi Department of Family and Community Medicine Faculty of Medicine, Public Health and Nursing, Universitas Gadjah Mada, Indonesia